The Way Of Nature: History & Truth In Heidegger's Late Thought - Lewis, Clay (Cosmos and History: The Journal of Natural and Social Philosophy, 2017)
This paper argues that Heidegger's deconstruction of metaphysics lends itself to an environmental ethic of non-violent ‘dwelling'. I trace the instrumental mode of ‘being-in-the-world' to the beginning of Western metaphysics in ancient Greece. The root of the problem is the technological understanding of things as objects and truth as objectivity. Heidegger indicates a more primordial understanding of truth as ‘event'. For Heidegger, the emergence of a non-instrumental way of life depends upon the extent to which the technological ‘framing' of nature nature is clearly perceived. I suggest that while Heidegger's post-foundational ethic does indeed envision a non-instrumental relation to nature, it remains unclear how such an alternative way of life may be politically achieved.